Digitalization of SMEs Using Financial Technology: A Systematic Literature Review - Thalita Syafira; Sambas Ade Kesuma; Keulana Erwin; Fahmi Natigor Nasution (CV. Ulil Albab Corp, 2026)
This study aims to analyze the role of Financial Technology (FinTech) in driving the digitalization of Micro, Small, and Medium Enterprises (MSMEs) through a systematic literature review. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines in the article selection process, with data sourced from the Scopus database. From an initial search yielding 41 articles, 11 articles meeting the inclusion criteria were selected for further analysis. Additionally, this study employs bibliometric analysis using the VOSviewer software to map relationships among concepts in the literature. The results indicate that FinTech serves as the primary enabler of SME digitalization through three key dimensions: behavioral factors, capabilities, and performance. Behavioral factors, such as perceived benefits and social influence, are critical determinants of technology adoption. Meanwhile, digital capabilities and financial literacy play a role in enhancing the effectiveness of FinTech adoption. In terms of performance, FinTech-based digitalization has proven capable of improving operational efficiency, transparency, and the competitiveness of SMEs. However, the existing literature still shows significant fragmentation, with most studies examining these dimensions separately. Therefore, this study contributes by integrating these three dimensions into a single comprehensive conceptual framework to explain the role of FinTech in the digitalization of SMEs. These findings are expected to serve as a foundation for further research and provide practical implications for SME stakeholders, policymakers, and FinTech service providers.